Determinación de la resistencia a la compresión de concretos de 3000 p.s.i utilizando probetas cilíndricas de (15x30) cm para edades de curado de 7 y 28 días, fabricados con materiales de la zona norte del departamento de sucre y cemento marca Tolcemento (2005)
One of the main functions of the interventoría is to look over the correct use of the building materials, for this it is necessary to have knowledge of the technical specifications and of the origin of these to realize a good quality control and to guarantee that the works are durable. In the Department of Sucre there are used materials extracted from the north Area and Maria's Mounts where there are located the quarries of Toluviejo (thick materials) and of the creeks of Pechelin and Palenquillo and located in the municipalities of Morroa and Sheep (thin materials). That's why in this grade work cm takes as targets to determine the resistance to the compression of concrete of 3000 P.S.I with cylindrical burettes of (15x30); to evaluate the evolution of the resistance to the compression of the concrete one with ages of treated of 7 and 28 days; and to realize the essays of grain, specific gravity, unitary mass, thickness and absorption to do the miscellany design. There were obtained results of laboratory tests that allowed to identify the characteristics of the thin and fat aggregations, the resistance to the compression of concrete of 3000 P.S.I prepared with materials of the north area (Subregions of the Mounts of Maria and Morrosquillo) of the Department of Sucre that will serve like a parameter to evaluate the resistance to the compression of this one concrete